The Strategy of the Sustainable Livelihoods for Beef Farmers in Bima Regency after the Flood Disaster in April 2021 - Kharismafullah Kharismafullah; Siti Azizah; Agus Budiarto (Faculty of Animal Science, Universitas Gadjah Mada, 2022)
The purpose of this study is to know the sustainable livelihood strategies of beef cattle farmers at the Bima region after the flood disaster. The research method used in this study is descriptive qualitative. The sampling method used the purposive sampling technique on 265respondents beef cattle farmersin the four research districts and 22 respondents as key informants consisting of the Head of the Livestock and Animal Health Service of Bima Regency, the Head of the West Nusa Tenggara Province (NTB) Forestry Service, the Head of the Bima Regency Agriculture Service, the Head of Technical Implementation Unit (UPT) of Animal Husbandry in the 4 research districts, the Head of agricultural UPT in the 4 sub-districts of the research location, 10 village heads in the 4 sub-districts where the research is located, and the head of the livestock group. Data collection methods consisted of field observations, structured interviews using questionnaires, in-depth interviews using snowball sampling techniques, and secondary data accessed at Bank Negara Indonesia (BNI) Bima Branch. The research locationconsists of 4 districts, among others: the Districts of Bolo, Madapangga, Woha, and Monta. The research location was selected based on the sub-districts that were worst affected by the floods. Primary data collection methods are observation and interviews while the secondary data collection method is by accessing the Department of Animal Husbandry and Animal Health in the Bima region and BNI. Data analysis using descriptive qualitative. The results of the research on sustainable livelihood strategies for beef cattle farmers to respond to flood disaster vulnerability are by implementing a strategy of utilizing available resource assets around the location of the livestock business which consists of human resource assets, natural resources, economic resources, physical resources and natural resources, power, social resources